Petrography, geochemistry, and cathodoluminescence of ancient white marble from quarries in the southern Phrygia and northern Caria regions of Turkey: Considerations on provenance discrimination. (December 2015) - Brilli, Mauro; Giustini, Francesca; Conte, Aida Maria; Lapuente Mercadal, Pilar; Quarta, Giovanni; Royo Plumed, Hernando; Scardozzi, Giuseppe; Belardi, Girolamo
Abstract: Marble quarries exploited in antiquity of the Denizli and Karacasu Basins (Turkey) were characterized by their petrography, carbon and oxygen isotopes, and cathodoluminescence. This study is an useful contribution for provenance studies of archeological artifacts composed of unknown marble. Marble quarries from the Hierapolis, Laodikeia, and Aphrodisias territories were considered; they constitute a homogeneous group of marble extraction districts. Collectively, they were among the most important sites for marble exploitation throughout antiquity from southwestern Anatolia, where only Afyon and Ephesus, which have already been studied extensively, were more important. In spite of that, the exportation of these marbles in ancient times has not yet been demonstrated. This is partially because their identification has never been fully addressed scientifically. Petrography, isotopes, and cathodoluminescence techniques used together are effective in discriminating among the study marbles. This could facilitate the determination of the provenance of these marbles in local monuments and artifacts. However, it could be difficult to determine the marble provenances in cases where a larger set of possible provenances should be taken into consideration. Highlights: A scientific database was created for Phrygian and Carian ancient marble quarries. Petrography, stable isotopes, and cathodoluminescence were used. The techniques used are effective in discriminating each quarry district. The database is useful for provenance determination of unknown marble artifacts.